PHARMACOLOGICAL STUDIES ON KW-1070 (PART 2) EFFECTS OF KW-1070 ON CARDIOVASCULAR, SMOOTH MUSCULAR AND URINARY EXCRETORY SYSTEMS - ISHII, HIDEE; SHUTO, KATSUICHI; OHMORI, KENJI; MARUMO, HIROFUTO; HIRAYAMA, TATSUYUKI; YAMANAMI, SADAYOSHI (CHEMOTHERAPY, 1981)
The pharmacodynamic actions of KW-1070 were studied in comparison with those of kanamycin (KM) and ribostamycin (RSM). The following results were obtained. 1. Blood pressure, respiratory rate and heart rate decreased after intraveneous administration of large doses of KW-1070, KM and RSM in anesthetized dogs, rabbits and cats. 2. Like KM and RSM, KW-1070 caused slight vasodilation in hind-leg of anesthetized dogs. 3. Contractile force and heart rate of isolated guinea-pig atria and heart were decreased by KW-1070, KM and RSM. 4. Like KM and RSM, KW-1070 reduced the muscular tonus and amplitude of spontaneous contraction in isolated rabbit intestine and rat uterus, and also suppressed the contractile responses to acetylcholine, nicotine, serotonin, Ba Cl2 and noradrenaline in isolated guinea-pig ileum, trachea and produce vas deferens. 5. Amounts of urine and Na+excretion were slightly decreased by KW-1070. 6. In the guinea-pig, rat and four mice strains test, multiple injections of KW-1070 failed to the antibodies of either class of Ig G or Ig E. From these results, it was concluded that the effects of KW-1070 on cardiovascular, smooth muscular and urinary excretory system were slight and nonspecific, similar to those of KM and RSM.